Implementation of Cartoon Puppet Media to Increase Students' Understanding of the Impact of Free Sex - Difa Ayu Sabila; Siti Muyana (Jurnal Counseling Care, 2024)
Based on the results of interviews conducted by researchers with guidance and counseling teachers at State Junior High School 3 Kebumen, some students do not have an understanding of the impact of free sex, marked by many students who claim to have watched adult videos that they should not have watched even since elementary school. This study aimed to determine the effectiveness of the implementation of cartoon puppet media group guidance services to increase understanding of the impact of free sex in junior high school. This research uses quantitative research, with an experimental research type and a One-Group Pretest-post-test research design. The research subjects were VIII grade State Junior High School 3 Kebumen students. With a research subject of 6 students who were given treatment selected by simple random sampling. Data collection techniques and instruments use questions related to understanding the impact of free sex. Data analysis techniques using normality test, homogeneity test, and Paired sample t-test. The results of the Paired sample t-test test show the value (Sig.) (2-tiled) of 0.002 <0.05, so Ho is rejected and Ha is accepted. Based on the research that has been carried out, it can be concluded that cartoon puppet media is effective for increasing students' understanding of the impact of free sex. Keywords: cartoon puppet media, casual sex